1999
DOI: 10.1111/j.1471-0528.1999.tb08186.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers for Down's syndrome in women who have had in vitro fertilisation: implications for antenatal screening

Abstract: To examine the Down's syndrome screening positive rate among in vitro fertilisation (IVF) pregnancies, we measured second trimester serum marker levels in singleton IVF pregnancies (cases) and in five non-IVF pregnancies (controls) matched to each case for gestational age, age of mother, and duration of storage of the serum sample. There were 15 1 IVF pregnancies in which alpha fetoprotein, unconjugated oestriol (LIE?), free P-human chorionic gonadotrophin (hCG) and total hCG were measured, 104 IVF pregnancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 9 publications
4
42
1
Order By: Relevance
“…Pregnancies conceived by assisted reproduction techniques (ART) have been reported to be associated with changes in the biochemical parameters of screening for DS, leading to an increased false-positive rate (FPR) in the second trimester (1)(2)(3)(4)(5)(6). The effect of ART on first-trimester Down screening, which combines maternal age, nuchal translucency thickness (NT), maternal serum free b subunit human chorionic gonadotropin (fb-hCG), and pregnancy-associated plasma protein-A (PAPP-A), has been examined, but the results have been inconclusive.…”
mentioning
confidence: 99%
“…Pregnancies conceived by assisted reproduction techniques (ART) have been reported to be associated with changes in the biochemical parameters of screening for DS, leading to an increased false-positive rate (FPR) in the second trimester (1)(2)(3)(4)(5)(6). The effect of ART on first-trimester Down screening, which combines maternal age, nuchal translucency thickness (NT), maternal serum free b subunit human chorionic gonadotropin (fb-hCG), and pregnancy-associated plasma protein-A (PAPP-A), has been examined, but the results have been inconclusive.…”
mentioning
confidence: 99%
“…However, associated syndromes such as Meyer-Rokitansky and McKusick-Kaufman syndromes have been reported. 2,7 Meyer Rokitansky syndrome is characterized by primary amenorrhea, uterine abnormalities, normal ovarian function and ovulation, and other congenital malformations (e.g., skeletal, renal). In our patient, there were no signs suggesting these syndromes.…”
Section: Case Reportmentioning
confidence: 99%
“…Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies. Several studies reported higher false-positive rate (FPR) compared to spontaneously conceived pregnancies [5,6,7,8,9,10,11], some studies found higher FPR even after correction for maternal age [12,13,14,15] and others reported similar FPR [16,17,18,19,20]. Whether the prevalence of fetal chromosomal abnormalities in ART pregnancies is different from naturally conceived pregnancies is however unclear.…”
Section: Introductionmentioning
confidence: 96%
“…In ART pregnancies maternal serum marker levels change during the first trimester affecting the risk assessment for DS [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies.…”
Section: Introductionmentioning
confidence: 99%